Speleothem stable isotopes from 670 - 240 ka ago at Cape Limeworks Cave 1, Robertson, South Africa - Kerstin Braun; Richard Cowling; Miryam Bar-Matthews; Alan Matthews; Avner Ayalon; Tami Zilberman; Mark Difford; R Lawrence Edwards; Xianglei Li; Curtis W Marean (PANGAEA, 2023)
We present stable oxygen and carbon isotope data and U-Th chronology data from five speleothems from Cape Limeworks Cave 1 near Robertson, Western Cape, South Africa (33.73S°, 19.77E°). The data set covers the time interval between 240 and 670 ka BP with hiatuses at 630-500 ka and 360-310 ka. The data are used to reconstruct climatic and environmental variability in an area known for its extraordinary plant biodiversity. Speleothems were extracted from the cave using a hammer and chisels and stable isotopes were analyzed at the Geological Survey of Israel using methods described in Bar-Matthews et al., (2003, Geochimica et Cosmochimica Acta, 67, 3181–3199. https://doi.org/10.1016/S0016-7037(02)01031-1) and Bar-Matthews et al., (1997, Quaternary Research, 47, 155–168. https://doi.org/10.1006/qres.1997.1883). U-series dating was done at the Geological Survey of Israel following methods described in Grant et al., (2012, Nature, 491(7426), 744–747. https://doi.org/10.1038/nature11593) and at the University of Minnesota following methods described in Edwards et al., (1987, Earth and Planetary Science Letters, 81, 175–192), Shen et al., (2012, Geochimica et Cosmochimica Acta, 99, 71–86. https://doi.org/10.1016/J.GCA.2012.09.018) and Cheng et al., (2013, Earth and Planetary Science Letters, 371–372, 82–91. https://doi.org/10.1016/j.epsl.2013.04.006).